PENATALAKSANAAN MOUTH PREPARATION PADA ANAK DENGAN KELAINAN JANTUNG BAWAAN TIPE ATRIAL SEPTAL DEFECT DI BAWAH ANESTESI UMUM: MOUTH PREPARATION MANAGEMENT IN CHILDREN WITH ATRIAL SEPTA DEFECT TYPE OF CONGENITAL HEART DISEASE UNDER GENERAL ANAESTHESIA - Inne Suherna Sasmita; Anissa Maya Kania; Kirana Lina Gunawan (TALENTA, 2011)
ASD (Atrial Septal Defect) is a congenital heart disease in the form of holes (defects) in the interatrial septum (septum between the right and left atrial cavity) due to failure of fusion that occurs during fetal interatrial septum. Septum does not close completely and allow blood to flow mixes the left and right atrium. The incidence is about 6.7% of all CHD in babies born alive. Patient 4-year-old girl with symptoms of multiple caries and general condition of ASD. Mouth care preparation of maintenance actions in the form of preventive measures such as fillings, fissure sealants, scaling, root planing as well as curative measures such as extraction of teeth in pediatric patients prior to surgery on his heart abnormalities. Management in the field of dentistry is important to prevent bacterial endocarditis. The purpose of this paper was to discuss the handling of mouth preparation in ASD patients. In Conclusion, mouth preparation in patients with cardiac abnormalities of type ASD is necessary before surgery on his heart abnormalities.